Pedagogical Mechanisms for Improving Technical Training of First League Football Players Through Simulator-Based Practice - Alisherov Muxiddin Madamin o‘g‘li (Next Scientists International Journal EIJP, 2026)
This article examines pedagogical mechanisms for improving the technical training of first league football players through simulator-based practice. The purpose of the study is to identify the didactic and methodological conditions under which training devices become an effective means of improving passing, receiving, shooting, balance, coordination, and technical decision-making in competitive football. The study uses system analysis, comparative pedagogical analysis, conceptual modeling, and synthesis of contemporary football-training literature. The results indicate that simulator-based practice is pedagogically effective when it is organized through diagnostics, individualization, staged progression, variability of tasks, game-like integration, and continuous feedback. The findings also show that training devices should not be reduced to mechanical repetition, because technical growth in football depends on the integration of perceptual-motor, coordinative, and cognitive components. The article concludes that simulator-based technical training for first league football players should be designed as a structured pedagogical system guided by evidence-based coaching principles and continuous performance monitoring.